Staging of rectal cancer – endosonography approach - Joksimovic N; Genadieva M; Andreevski V; Todorovska B; Curakova E; Isahi U; Serafimoski V (My University, 2012)
INTRODUCTION This study is a prospective clinical investigation that includes 701 patients aged on average 55.7 years with symptoms such perirectal pain, rectal bleeding, and change in bowel habit and tenesmus that had been investigated at the Clinic. Rectal cancer was diagnosed by endoscopy and pathohistologically confirmed in 404 cases. AIM The aim of the study was to evaluate the use of endorectal ultrasound in demonstration of the tumour, extension into per rectal fat and lymph node involvement. MATERIAL AND METHODS Demonstration of tumor, extension into perirectal fat and lymph node involment were evaluated. Tumors were succesfully imaged by endorectal ultrasound. Ultrasonic examination was performed with a 7.5 MHz blind endorectal probe. Patients were examined in the left lateral decubitus position. No complications were encountered. However, five patients did have minimal rectal bleeding after the examination. No patients experienced pain, although many encountered mild discomfort. RESULTS According to the endosonographical results patients were divided into 3 groups: operable, consisting of 192 pts (27.4%), unoperable group of 212 pts. (30.2%) and control group with 297 pts (42.4%). All patients from the first group endosonographicaly classified as operable rectal carcinoma were compared with the definite surgical diagnosis. Endosonographicaly 57 pts (14%) had I-st degree, 135 pts (33.5%) had II-nd degree. The group classified as inoperable rectal tumours 212 pts (52.5%) is compared with the operative findings of palliative operated patients, by reason of complication due to the primary process (ileuses) 75 pts were operated, and endosonographic diagnosis was confirmed by the operation findings. The control group of patients (297 pts) which was endosonographicaly classified to be without signs of primary and secondary neoplasmatical process in the rectal wall, was compared with all the findings got by rectoscopy, colonoscopy and their combination with histology. The ovaries Adenocarcinoma ovarii were found in 54 pts (18.5 %), Ovarial cyst in 26 pts. (9 %), Myoma uteri in 32 pts. (10.5 %), Adeocarcinoma uteri in 67 pts (23 %), Adenocarcinoma prostatae in 44 pts (15 %), Adenoma prostate in 33 pts (11%), IBD in 31pts (10 %), perirectal abscesses in 7 pts (2.5 %), M. Hirschprung’s disease in 2 pts, and torsion of the sigmoid colon in one patient. CONCLUSION However, transrectal sonography as a usable supplementary method has to provide approximate sensitivity as the method to which it is supplementary, in fact to be able to detect the lession that was proved beyond doubt in this study. The results suggest that transrectal sonography has an importent role in the determination of the operability of rectal malignoma, following and predicting of the degree of infiltration and determining of the precise borders of the intramural infiltration. The utility of blind endosonography (BUS) is evident, the method is noninvasive, and there are no contraindications, permits fast, easy and precise evaluation of the rectal cancer extension as well as the diseases of the neighbouring organs.
Ендосонографски пристап во стејџингот на ректалниот карцином